2000
DOI: 10.1021/om000310q
|View full text |Cite
|
Sign up to set email alerts
|

[(dcpe)Pt(ECp*)2] (E = Al, Ga):  Synthesis, Structure, and Bonding Situation of the First Aluminum(I) and Gallium(I) Complexes of Phosphine-Substituted Transition Metal Centers

Abstract: Herein we describe the first phosphine-substituted transition metal complexes with terminal coordinated Cp*E ligands (E ) Al, Ga; Cp* ) pentamethylcyclopentadienyl). The reaction of [(dcpe)Pt(H)(CH 2 t-Bu)] (dcpe ) bis(dicyclohexylphosphino)ethane) with Cp*E yields the tetrahedrally coordinated complexes [(dcpe)Pt(AlCp*) 2 ] (1) and [(dcpe)Pt(GaCp*) 2 ] (2), respectively. Quantum-chemical DFT calculations on the model complexes [(dhpe)Pt-(AlCp) 2 ] (1M) and [(dhpe)Pt(GaCp) 2 ] (2M; dhpe ) diphosphinoethane) ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 30 publications
0
31
0
2
Order By: Relevance
“…However, compounds of that kind do exist, for example, [Pt(ECp*) 2 (dcpe)] (dcpe = bis(dicyclohexylphosphino)ethane), and were synthesized by trapping the in situ formed [L 2 Pt] with stoichiometric amounts of ECp*. [24,25] In the presence of stronger p-acceptor ligands the dinuclear molecular structure M 2 Ga 3 is retained and disubstituted species similar to 5 are formed. Thus, the reaction of Pt 2 Ga 5 with an excess of CO or CNtBu yields the complexes [Pt 2 (CO) 2 (m 2 -GaCp*) 3 ] (6) and [Pt 2 (CNtBu) 2 (m 2 -GaCp*) 3 ] (7), respectively (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, compounds of that kind do exist, for example, [Pt(ECp*) 2 (dcpe)] (dcpe = bis(dicyclohexylphosphino)ethane), and were synthesized by trapping the in situ formed [L 2 Pt] with stoichiometric amounts of ECp*. [24,25] In the presence of stronger p-acceptor ligands the dinuclear molecular structure M 2 Ga 3 is retained and disubstituted species similar to 5 are formed. Thus, the reaction of Pt 2 Ga 5 with an excess of CO or CNtBu yields the complexes [Pt 2 (CO) 2 (m 2 -GaCp*) 3 ] (6) and [Pt 2 (CNtBu) 2 (m 2 -GaCp*) 3 ] (7), respectively (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Diese Verbindung weist jedoch eine zusätzliche Pt-Al-p-Rückbindung auf, die den geringen Pt-Al-Abstand bewirkt. [18] Abbildung 1. Molekülstruktur von 2 (ohne Wasserstoffatome, thermische Ellipsoide bei 50 % Wahrscheinlichkeit).…”
Section: Holger Braunschweig* Katrin Gruss Und Krzysztof Radackiunclassified
“…[28] It was shown that compound 4a can act as a building block for the synthesis of dinuclear complexes affording [Mo 2 (CO) 6 [29,30] The unsaturated 14 VE fragment [(dcpe) 2 Pt] is thermally formed from [(dcpe) 2 PtH(neopentyl)] and trapped in the presence of E I R ligands (Scheme 2). An unsaturated carbonyl system which has been studied in more detail is the reaction of GaCp* with the multiple bonded dimeric complexes [CpM(CO) 2 ] 2 (M ϭ Mo, W).…”
Section: Carbonyl Complexes M a (Co) B (Er) Cmentioning
confidence: 99%